Chemical composition and antioxidant activities of different parts of Ficus sur - Kossivi Issa Saloufou; Pakoupati Boyode; Oudjaniyobi Simalou; Kodjo Eloh; Kokou Idoh; Mamatchi Melila; Outéndé Toundou; Kafui Kpegba; Amegnona Agbonon (Shahrekord University of Medical Sciences, 2018)
Introduction: Ficus sur is a plant widely used in traditional pharmacopoeia in Togo. So, this study aimed the assessment of antioxidant properties and identification of some compounds from the ethanolic extracts of different parts of the plant (leaves, fruits, roots, and barks). Methods: The phenolic and flavonoid contents of the ethanolic extracts of different organs of Ficus sur were assessed using conventional known methods. The DPPH radical scavenging and the ferric-reducing antioxidant power (FRAP) assays were used to highlight the antioxidant activities. The different extract samples were also analysed by liquid chromatography coupled to a quadrupole-time of flight mass detector (ESI-QTOF). Results: Total phenolic contents (TPCs) for 1 mg of dry extract ranged from 489.40 ± 7.48 μg GAE (gallic acid equivalents) for the bark to 62.34 ± 2.66 μg GAE for unripe fruits. The bark exhibited the highest flavonoid content, which was closed to 90.20 ± 3.72 μg QE (quercetin equivalents)/mg of dry extract. The radical scavenging activities of the bark and unripe fruits were 56.50 ± 0.29 and 7.3 ± 0.30 μg QE/mg of dry extract, respectively. In the same order, the FRAP values of the two organs were 104.57 ± 4.75 and 19.61 ± 0.22 μmol FeSO4 Eq/mg of dry extract. Many compounds including notoginsenoside R10; 4',5,7-trihydroxyflavan-3-ol; catechin; and boviquinone 4 were identified. Conclusion: The various organs of Ficus sur are a source of bioactive compounds especially phenolic compounds and flavonoids with antioxidant activity.